2014
DOI: 10.1002/jaba.154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serial and concurrent training on acquisition and generalization

Abstract: Despite a large body of research demonstrating that generalization to novel stimuli can be produced by training sufficient exemplars, the methods by which exemplars can be trained remain unclear. The purpose of the current study was to evaluate 2 methods, serial and concurrent presentation of stimuli, to train sufficient exemplars. Five preschool children with developmental delays were taught to identify letters or letter sounds using serial and concurrent presentation. Generalization to untrained exemplars wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
1
24
2
2
Order By: Relevance
“…These comparison studies allow researchers to evaluate relative efficiency, and may provide helpful information to practitioners as to the training arrangement that is most beneficial for the consumers they serve. Previous studies directly compared the effects of S‐MET and C‐MET (e.g., Panyan & Hall, ; Schroeder & Baer, ; Schroeder, Schuster, & Hemmeter, ; Wunderlich, Vollmer, Donaldson, & Phillips, ). Overall, these studies have shown acquisition of targeted responses with both S‐MET and C‐MET, but more successful stimulus generalization during C‐MET.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These comparison studies allow researchers to evaluate relative efficiency, and may provide helpful information to practitioners as to the training arrangement that is most beneficial for the consumers they serve. Previous studies directly compared the effects of S‐MET and C‐MET (e.g., Panyan & Hall, ; Schroeder & Baer, ; Schroeder, Schuster, & Hemmeter, ; Wunderlich, Vollmer, Donaldson, & Phillips, ). Overall, these studies have shown acquisition of targeted responses with both S‐MET and C‐MET, but more successful stimulus generalization during C‐MET.…”
mentioning
confidence: 99%
“…Overall, these studies have shown acquisition of targeted responses with both S‐MET and C‐MET, but more successful stimulus generalization during C‐MET. For example, Wunderlich et al () evaluated the relative effectiveness (as measured by sessions to mastery) of S‐MET and C‐MET on the acquisition and generalization of tacts of letters or letter sounds for five participants with developmental disabilities. During S‐MET, training occurred for one of three training exemplars.…”
mentioning
confidence: 99%
“…Another limitation related to the procedures in Experiment 1 is that generalization across novel packages was not assessed. However, generalization involves the spread of reinforcement effects from trained stimuli to novel stimuli sharing similar physical or functional properties (Wunderlich, Vollmer, Donaldson, & Phillips, ). Therefore, it could be argued that when responding comes under the control of the safe and unsafe features present in the exemplars during training, the presentation of novel safe and unsafe packages that share these features should also occasion the same responses.…”
Section: Discussionmentioning
confidence: 99%
“…Sessions consisted of 12 trials of teaching images, with six trials of one target (e.g., fox) and six trials of the other target (e.g., skunk) in the pairing (i.e., concurrent sequencing; Schroeder & Baer, ; Wunderlich, Vollmer, Donaldson, & Phillips, ). We presented three exemplars for each target twice in a quasirandom fashion and did not present a single target more than twice in a row.…”
Section: Methodsmentioning
confidence: 99%